Real-time quantitative polymerase chain reaction (RO-PCR) using the LightCycler: a rapid, high-throughput method for detecting and quantifying fusion transcripts in childhood leukaemias for disease stratification and prognostication. - Loh, L.H. (2013)
Annals of the Academy of Medicine, Singapore